Oncolytic adeno-immunotherapy modulates the immune system enabling CAR T-cells to cure pancreatic tumors - Rosewell Shaw, Amanda (Commun Biol, 2021)
High expression levels of human epidermal growth factor receptor 2 (HER2) have been associated with poor prognosis in patients with pancreatic adenocarcinoma (PDAC). However, HER2-targeting immunotherapies have been unsuccessful to date. Here we increase the breadth, potency, and duration of anti-PDAC HER2-specific CAR T-cell (HER2.CART) activity with an oncolytic adeno-immunotherapy that produces cytokine, immune checkpoint blockade, and a safety switch (CAdTrio). Combination treatment with CAdTrio and HER2.CARTs cured tumors in two PDAC xenograft models and produced durable tumor responses in humanized mice. Modifications to the tumor immune microenvironment contributed to the antitumor activity of our combination immunotherapy, as intratumoral CAdTrio treatment induced chemotaxis to enable HER2.CART migration to the tumor site. Using an advanced PDAC model in humanized mice, we found that local CAdTrio treatment of primary tumor stimulated systemic host immune responses that repolarized distant tumor microenvironments, improving HER2.CART anti-tumor activity. Overall, our data demonstrate that CAdTrio and HER2.CARTs provide complementary activities to eradicate metastatic PDAC and may represent a promising co-operative therapy for PDAC patients.